Redesigning an Information System that Reduces Health Care Accessibility Effort and Increases User Acceptance and Satisfaction: A Comparative Effectiveness Study. Issue 1 (3rd October 2018) - Long, Sandra; Monsen, Karen A.; Pieczkiewicz, David; Wolfson, Julian; Khairat, Saif
Objectives: This research tackles a critical issue in modern health care systems—namely, to determine if creating a user-centered health information system that is easy to utilize would lead to consumers who are more satisfied and more likely to accept the system. Materials and Methods: The health information system is a consumer service center that receives inquiries from consumers on how to find and pay for care. To understand if a system designed to decrease effort results in satisfaction, we redesigned the system, deployed it for 3 months, and then compared consumer satisfaction results to a control group. Satisfaction and Net Promoter surveys were provided to consumers who used the control system and consumers using the redesigned system. Results: This study was completed over a 6 month continual time period where over 100, 000 consumer interactions took place. Using 11 different metrics and data from over 5, 000 random system users, it was shown that consumers were more satisfied with an information system designed to reduce their administrative effort. Discussion: While not all consumer survey results were statistically significant, they all showed a shift towards improved satisfaction with the health care system. Statistically, it was shown that there was a dependency between the design of the system to provide information and many needs of the consumers. Conclusion: A health care system designed to reduce effort in accessing care results in improved consumer satisfaction. Consumers are also more likely to trust the assistance provided by the organization.